Measuring the clinical competencies of UiTM nursing students / Rashidah Shahruddin, Noraini Hashim and Siti Khuzaimah Ahmad Sharoni - Shahruddin, Rashidah; Hashim, Noraini; Ahmad Sharoni, Siti Khuzaimah (2006)
Measuring the clinical competencies of UiTM's nursing students: Aims of the study: The purpose of this study is to look at competence, as performance of clinical skills and the ability of the nursing students to perform basic clinical skills using a predetermined criteria for clinical evaluation adapted from Bondy (1983). The study identifies five basic clinical skills and the selections based on Henderson's activities of daily living (1978) that encompassed physiological, psychological and spiritual needs of the clients. Background: Most of the previous studies have developed a plethora of tools in an attempt to improve objectivity in clinical evaluation, and previous researchers have suggested that criterion-referenced tools are the most effective in determining student performance in the clinical placements. Despite numerous tools available to measure clinical competency from the wealth of related studies, the literature/ reviews did not reveal a tool with a numerical score that met all the requirements. Some studies have highlighted that the requirements of essential cognitive, psychomotor and affective skills acquisition enhancement is through clinical experiences and with decision making and critical thinking being part of the process. A/iiumber of researchers have indicated the need to address spiritual and'' psychological competencies in nurse education. This with regards to specific needs rather than a generalized concept on how a patient should be treated as the provision of care could head towards insensitive to the needs of individuals from diverse culture and religions.